Nutrition-Related Clinical Decision Making of Pediatric Oncology Nurses. (September 2019) - Lulloff, Amanda J.; Vessey, Judith A.; Bashore, Lisa; Gregas, Matt
Children with a cancer diagnosis have risk factors leading to unique nutritional challenges. Malnutrition in this population is correlated with worse patient outcomes. Nurses are responsible for providing holistic care to their patients; however, the quality of nutritional assessments by pediatric oncology nurses is unknown. The purpose of this study was to investigate staff nurses' clinical decision making regarding nutritional assessment of children with cancer. A web-based survey composed of a demographic form, vignettes of patients with diverse nutritional status and the New General Self-Efficacy Scale, was distributed to members of the Association of Pediatric Hematology Oncology Nurses. Participants were also asked to rate their confidence in responses as well as select key nutritional cues. Nurses were significantly more likely to under-rate the nutritional status and select far fewer cues than the experts. Further research regarding nutritional assessment is warranted. Evidenced-based guidelines for nutritional assessment of children with cancer should be developed to ensure the highest quality of care is provided to this patient population.